Balance Optimization of Energy Consumption and Running Time for Urban Metro Trains - WU Xiao-gang; CHEN Yu; GUO Hao-qi; DU Jiu-yu (Journal of Harbin University of Science and Technology)
Abstract:In view of the energysaving and efficient operation of metro trains (MTs) requirements, this paper analyzes the change trend of MT energy consumption with cruise speed when the power of auxiliary devices of metro train changes based on the calculation model of traction energy consumption of MT. The linear weighting method is used to quantitatively calculate the optimal cruise speed condition corresponding to the energy consumption and running time of the whole MT, and the energy saving potential of the MT is analyzed from a quantitative perspective to provide reference for the energy saving and efficient operation of the MTs. The results show that under different auxiliary device power conditions, the optimized cruise speed of the MT can effectively reduce the energy consumption of the whole MT, and the maximum energy saving potential can reach 19.13%.